Unraveling the Threads of Difficult History in the Classroom: A Systematic Literature Review - Ahmad, Tsabit Azinar; Mulyana, Agus; Darmawan, Wawan; Wiyanarti, Erlina (History Department, Semarang State University and Historian Society of Indonesia, 2024)
This systematic literature review aims to comprehensively examine and synthesize existing research on teaching difficult history in the classroom. Difficult history includes emotionally charged, controversial, or challenging topics for educators and students. Twenty-three publications from the Scopus database from 2014-2023 were selected for review using PRISMA 2020 guidelines. Then, four research questions were used to guide the review and analysis centered on difficult history content, pedagogical approaches, teachers’ challenges to offering a comprehensive understanding of difficult history learning in schools, and the impact of difficult history on students. Reviews reveal that scholars are increasingly interested in studying difficult historical topics and highlighting dark events in various regions worldwide. Teaching difficult history requires multiple pedagogical approaches, including affective learning, experiential learning, and inquiry-based learning. Teaching difficult history contributes to empathy, critical thinking skills, and historical consciousness to encourage students to connect past events to present-day issues.Reviu literatur sistematis ini bertujuan untuk mengkaji secara komprehensif dan mensintesis penelitian yang ada tentang pengajaran sejarah pelik (difficult history) di kelas. Sejarah yang sulit mencakup topik-topik yang bermuatan emosional, kontroversial, atau menantang bagi pendidik dan siswa. Dua puluh tiga publikasi dari database Scopus pada tahun 2014-2023 dipilih untuk ditinjau menggunakan pedoman PRISMA 2020. Reviu dan analisis dipandu oleh empat pertanyaan penelitian, yang berpusat pada konten sejarah pelik, pendekatan pembelajaran, tantangan guru pada pembelajaran sejarah pelik di sekolah, dan dampak sejarah pelik pada siswa. Reviu mengungkap bahwa para sarjana semakin tertarik untuk mempelajari topik-topik sejarah yang pelik, serta menyoroti beragam peristiwa kelam di berbagai wilayah di seluruh dunia. Mengajarkan sejarah pelik memerlukan berbagai pendekatan pedagogi, termasuk pembelajaran afektif (affective learning), pembelajaran berdasarkan pengalaman (experiential learning), dan pembelajaran berbasis inkuiri. Mengajarkan sejarah pelik berkontribusi pada empati, keterampilan berpikir kritis, dan kesadaran sejarah untuk mendorong siswa menghubungkan peristiwa masa lalu dengan isu-isu masa kini.